Role of sympathetic nervous system in non-ischaemic ventricular arrhythmias. Issue 2 (February 1982) - Coumel, P; Rosengarten, M D; Leclercq, J F; Attuel, P
Abstract : Propranolol and nadolol were used in two groups of patients having ventricular arrhythmias. The two groups were characterised by differences in sympathetic drive. The 10 non-adrenergic patients had idiopathic, monomorphic extrasystoles (isolated with fixed coupling or in pairs or salvoes) arising from the right ventricle or the septum. These extrasystoles were chronic and benign, with a slightly increased daytime frequency (day:night = 1.6). They disappeared on exercise. The nine adrenergic patients had less frequent but more complex polymorphic ventricular extrasystoles, and rapid and irregular tachycardias which were resistant. They occurred predominantly during the day and were associated particularly with stress and exercise. They were either idiopathic, or coexisted with mitral valve prolapse (three cases) or hypertrophic subaortic stenosis (one case) in young patients (mean age, 32 years) who did not have coronary heart disease. Nadolol was more effective than propranolol in controlling the arrhythmia, heart rate, and variations in sinus rhythm in the adrenergic group, while the arrhythmia was not controlled in the non-adrenergic group. Using clinical variables, comparison of the frequency of extrasystoles by day and night, and assessment of the antiarrhythmic effect of beta-blockers, the role of the sympathetic tone in non-ischaemic ventricular arrhythmias may be elucidated.